FireReady Challenge: A 2D Gamified Prototype for Community Fire Safety Preparedness - Rabeah Md Zin; Ahmad Amru Mohamad Zaid; Zailah Salamon; Adi Irfan Che Ani; Nur ‘Amirah Mhd Noh (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2026)
Fire protection remains a critical public concern, as fire-related incidents continue to cause substantial property damage, personal injuries, and loss of life. Although public awareness campaigns and routine safety drills are widely implemented, conventional didactic training methods such as posters, presentations, and demonstrations often fail to generate lasting comprehension or meaningful behavioural change. To address this gap, this paper presents the FireReady Challenge, a 2D gamified learning prototype designed to enhance community awareness and preparedness in fire safety. The game adopts the ADDIE instructional model to systematically translate key learning objectives into interactive digital experiences focused on hazard identification, safe evacuation procedures, emergency communication readiness, and proper fire extinguisher use. Gamification elements, including points, badges, real-time feedback, and time-bound missions, are embedded to strengthen motivation and user engagement. This concept design demonstrates an innovative approach to ICT-based fire safety education for community dissemination. Future research will involve pilot-scale deployment and empirical validation to evaluate learning outcomes, usability, and user acceptance.